La literatura concentracionaria: universalidad, representación y memoria / The Literature of Concentration Camps: Universality, Representation and Memory (Vegueta: Anuario de la Facultad de Geografía e Historia, 2019)
El artículo supone una aproximación al fenómeno universal de la literatura concentracionaria. A partir del análisis de textos escritos por supervivientes de los campos nazis, el Gulag o los campos de internamiento franceses, se intentan esbozar las principales características temáticas, formales y pragmáticas de este tipo de escritura.This paper examines the universal phenomenon of concentration camp literature. The article departs from texts written by individuals who survived Nazi concentration camps, the Soviet Gulag, or French internment camps, with the aim of reflecting upon the formal, thematic and pragmatic traits that define this type of literature.